Arboviruses emerging in Brazil: challenges for clinic and implications for public health - Maria Rita Donalisio; André Ricardo Ribas Freitas; Andrea Paula Bruno Von Zuben
ABSTRACT Arboviruses have been emerging in different parts of the world due to genetic changes in the virus, alteration of the host and vector population dynamics, or because of anthropogenic environmental factors. These viruses' capacity for adaptation is notable, as well as the likelihood of their emergence and establishment in new geographic areas. In Brazilian epidemiologic scenario, the most common arboviruses are DENV, CHIKV, and ZIKV, although others may spread in the country. Little is yet known of the impact of viral co-circulation, which would theoretically result in more intense viremia or other immunological alterations that could trigger autoimmune diseases, such as Guillain-Barré syndrome. The impact on morbidity and mortality intensifies as extensive epidemics lead to a high number of affected individuals, severe cases, and implications for health services, mainly due to the absence of treatment, vaccines, and effective prevention and control measures.